KELAYAKAN BAHAN AJAR BERBASIS TEKNOLOGI PADA MATA PELAJARAN MATEMATIKA - Trimurtini Trimurtini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The teaching material based on technology that have been made and studied were teaching material which are completed with technology application related with subject matter. Technology application can be applied in daily life and also other sciences. Research area covers mathematics material of VII grade of Junior High School. The aims of this research are: (1) Identifying technology application which can be related with mathematics study materials, (2) Describing the forms of mathematics teaching aid based on technology, (3) To know the feasibility of mathematics teaching aid based on technology that was completed with contextual problem, so it can raise student’s motivation. The data collected by documentation, observation and questionnaire. Then the data analyzed trough 3 stages: reducing data, presenting data and verification, and also with descriptive analysis qualitative. The results of the research are: (1) Technology application that can be related with the study of mathematics subject matter is technology in daily life and also is a mathematics concept application in other concepts or other sciences. Technology application that related with subject materials in the teaching aid can be presented in the beginning or in the exercises. (2) Description of mathematics teaching materials forms are technology application from the materials which are fulfilling the curriculum criteria suitable with content standard, (3) Teaching aid based on technology completed with contextual problems in daily life and mathematics concept application in other concepts as a form of technology application can fulfilling eligibility test, that covering material aspect, material presentation aspect and language aspect.